Comparison of two tonality estimation methods used in a psychoacoustic model - Chen, Hao; Taghipour, Armin; Edler, Bernd (Proc. 4th IEEE Int. Conf. Audio, Lang., Image Process. (ICALIP), 2014)
Perceptual audio codecs apply psychoacoustic principles such as masking effects of the human auditory system in order to reduce irrelevancies in the input audio signal. Psychoacoustic studies show differences between masking strength of tonal and noise maskers: the masking effect of narrowband noise is stronger than that of a tone which has the same power and is placed in the center frequency of the noise. In this paper, two tonality estimation methods are discussed which are implemented in a filter bank based psychoacoustic model. The first method is called Partial Spectral Flatness Measure (PSFM) and the second is referred to as Amplitude Modulation Ratio (AM-R). The psychoacoustic model uses a set of complex band-pass filters. It was designed according to the temporal/spectral resolution of the human auditory system, and takes into account post masking as well as the spreading effect of individual local maskers in simultaneous masking. This paper describes the model, tonality estimation methods and their implementation. The estimators are compared to each other by subjective tests. The results are presented and discussed.<br